Minority hair tax: pricing bias in haircare products - Yacine N. Sow, BA; Amanda A. Onalaja-Underwood, MD; Tiaranesha K. Jackson, MPH; Susan C. Taylor, MD; Temitayo A. Ogunleye, MD (Wolters Kluwer, 2023)
Background:. Black haircare is an estimated $2.51-billion-dollar industry. Black women spend 9 times more on ethnic hair products than non-Black consumers. The haircare industry has adapted to these market trends by developing products catering to the needs of "natural hair," referring to curly to tightly coiled hair texture that has not been chemically straightened with a relaxer. Anecdotally, natural haircare products are relatively expensive. Objective:. We aimed to investigate texture-based price differences for haircare products targeting coily/curly compared to straight hair types. Methods:. Data were collected in August 2022 from 6 brands available on www.amazon.com. After stratifying the data by manufacturer, hair texture, and average price/oz, we used 2 sample t-test with equal variances to examine cost differences. Results:. Overall, there was a significant difference in average price/oz between all coily/curly and straight hair products, with coily/curly hair products being more expensive. When stratified by manufacturer, one leading US manufacturer sold coily/curly hair products at a higher price ($0.66/oz ±$0.05) compared with straight hair products ($0.46/oz ±$0.04), t14 = 2.8967, P < 0.0134. Limitations:. A small sample size of only shampoos and conditioners were analyzed, which may not represent the number of haircare products that consumers use. Conclusion:. Pricing policies should ensure that all individuals have access to effective, affordable haircare products. Dermatologists should also be cognizant of pricing differences to direct patients with natural hair to fairly priced products.